Internationally Adopted Children With Unilateral Cleft Lip and Palate—Consonant Proficiency and Perceived Velopharyngeal Competence at the Age of 5. (July 2020) - Larsson, AnnaKarin; Miniscalco, Carmela; Mark, Hans; Schölin, Johnna Sahlsten; Jönsson, Radi; Persson, Christina
Objective: To compare consonant proficiency, consonant errors, and the perceived velopharyngeal (VP) competence in internationally adopted (IA) children with unilateral cleft lip and palate (UCLP) and nonadopted (NA) children with the same cleft–palate type at age 5. Design: Case–control study based on phonetic transcriptions of standardized speech recordings of 5-year-olds at a tertiary hospital. Participants: Twenty-five IA children were compared to 20 NA children. All consecutive patients at a cleft lip and palate center participated. Main Outcome Measure(s): Consonant proficiency was measured using percentage consonants correct, percentage consonants correct–adjusted for age, percentage correct place, percentage correct manner, and consonant inventory. Cleft speech characteristics (CSCs), developmental speech characteristics (DSCs), and the perceived VP competence were also measured. Results: The IA children had significantly lower values for all consonant proficiency variables ( p < .05) and a smaller consonant inventory ( p = .001) compared to the NA children. The IA children had a higher frequency of CSCs (IA = 84%, NA = 50%, p < .05) and DSCs (IA = 92%, NA = 65%, p = .057), and twice as many IA children as NA children had perceived VP incompetence (IA = 52%, NA = 25%, p = .17). Conclusions: Severe speech disorder was more common in IA children than in NA children at age 5. Most importantly, the speech disorders seem to be not only cleft-related. More detailed speech assessments with a broader focus are needed for IA children with UCLP. Longitudinal studies are recommended to further investigate the impact of speech difficulties in IA children's daily lives.